The Effectiveness of Problem-Based Learning Student Worksheets in Enhancing Critical Thinking Skills in Fourth-Grade Science Subjects - Ni Ketut Warmi Juliantari; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2024)
Students' critical thinking skills are influenced by teachers' limited competence in implementing problem-solving-oriented learning. Therefore, this study aims to analyze the effectiveness of problem-based learning (PBL) student worksheets (Lembar Kerja Peserta Didik - LKPD) in improving critical thinking skills in fourth-grade science subjects (Ilmu Pengetahuan Alam dan Sosial - IPAS) at the elementary school level. The development model used in this study follows the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The research employs a one-group pretest-posttest design, with 15 fourth-grade students as the study participants. Data collection methods include questionnaires and multiple-choice tests. The research instruments were developed based on a structured blueprint to ensure alignment with research guidelines. Content validity was assessed using Gregory’s formula with expert judgment, while item validity was tested using the product-moment correlation method. Reliability testing was conducted using the Cronbach’s Alpha method, as the data consisted of polytomous scores ranging from 0 to 4. Data analysis was carried out using both qualitative and quantitative approaches, including descriptive and inferential statistical analysis. The effectiveness test was conducted using a paired sample t-test in SPSS. The results indicated that the Sig. (2-tailed) value was 0.000 < 0.05, leading to the conclusion that the PBL-based student worksheets are significantly effective in enhancing the critical thinking skills of fourth-grade elementary school students.